Поиск и идентификация молодых звездных объектов в инфракрасном пылевом пузыре N19 - Alisher, A.M.; Aslan, D.; Turekhanova, K.M. (Вестник. Серия физическая, 2023)
In last times the dynamic development of astrophysics studied the interaction of matter and radiation on cosmos space, as well as the appearance of new possibilities of observation of celestial bodies allow to investigate the physical processes in the interstellar medium in detail. The density and quantity of interstellar gas and dust determine the possibility of new star formation, meanwhile star changes the properties of the surrounding interstellar medium, they heat it, support the continues movement of gas and supplement the medium with their own matter and change their chemical composition. In the present work the first searches of young stellar objects were carried out in the region of the infrared duct bubble N19 and also there were created the program for searching of new stellar objects in computer simulation by MatLab. 11 objects were attributed to the young stars of I class by the found sources of infrared radiation, 26 objects to the II class and 20 objects are regarded to the young stars at the stage of transition disks. As a result, “a color-color” diagram for young stellar objects candidates detected near the infrared dust bubble N19 was constructed. In addition, there were analyzed the ranges of variation of the color indices and that diagram allows to determine the new criteria for determination of the new star objects in accordance with the stage of their evolution.
Keywords: инфракрасный пылевой пузырь N19; межзвездная среда; молодые звездные объекты; звезда